Modern approaches to warehouse logistics management - Shyshkin, Viktor; Onyshchenko, Oksana; Cherniak, Kateryna (Management and Entrepreneurship: Trends of Development, 2020)
The article aims to systematize the main approaches to the definition of warehouse concept. It analyses modern approaches to warehouse logistics management and identifies the main advantages and disadvantages of their use in the enterprise logistics system. In the article the theoretical aspects of warehouse logistics are revealed and the existing approaches to warehouse logistics management of modern enterprises are analysed. The mechanism of warehouse logistics management was explored as well as the ways to improve its efficiency were suggested. Methodology: general scientific theoretical and empirical methods of research as analysis and generalization, methods of observation and comparison, analytical, grouping of data were used. The urgency and expediency of warehouse modification at Ukrainian enterprises is substantiated. The relevance of the article is the need to adopt domestic enterprises to a qualitatively new system of economic relations and mechanisms of competitive relations of the modern market as well as the urgent necessity to adapt business entities to uncertainty in order to improve their management organization strategies, including warehouse logistics. The practical value of the research results is that the proposals and recommendations for improving the warehouse logistics management process identified in the paper can be used by enterprises in order to use modern innovative approaches to improving the quality of logistics processes. In addition, the implementation of the proposed provisions will significantly reduce the logistical costs of the enterprise and optimize the activities of any production company.JEL Classification: D24, L23.